Using Standards-Based and Evidence-Based Content in Early Childhood Professional Development - Rashida Banerjee; Harvey Rude (Social Welfare: Interdisciplinary Approach)
Converging empirical evidence has identifi ed key components of effective practices for providing high-quality services to young children and their families. The article describes the components of professional development that result in well qualifi ed, well-trained and effective early childhood professionals who can implement evidence-based practices to improve outcomes of young children and their families. Specifi cally, standards-based and evidence-based professional development competencies developed and guided by national and state agencies are discussed.